EVERYDAY PRACTICES AND DECLARATIVE: CONTRADICTORY RELATIONSHIP OF YOUNG PEOPLE TO ALCOHOL - T. V. Smirnova; V. V. Maslyakov; R. G. Smirnov (Вестник университета)
The problem of youth perception of alcohol consumption has been considered. The authors carried out a survey using the questionnaire method (N=620), the respondents were residents of Moscow and the Moscow region aged 14-30 years. According to the results of the study a conclusion has been made that the perception of alcohol consumption has a double, contradictory character. On the one hand, the respondents indicate a pronounced negative attitude to both alcohol consumption and consumers. At the same time, modern statistical data and a milder attitude of the respondents to personal alcohol consumption specify the superficiality of the negatively declared perception.